2013
DOI: 10.1103/physreve.88.062309
|View full text |Cite
|
Sign up to set email alerts
|

Far-from-equilibrium sheared colloidal liquids: Disentangling relaxation, advection, and shear-induced diffusion

Abstract: Using high-speed confocal microscopy, we measure the particle positions in a colloidal suspension under large-amplitude oscillatory shear. Using the particle positions, we quantify the in situ anisotropy of the pair-correlation function, a measure of the Brownian stress. From these data we find two distinct types of responses as the system crosses over from equilibrium to far-from-equilibrium states. The first is a nonlinear amplitude saturation that arises from shear-induced advection, while the second is a l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 61 publications
(104 reference statements)
1
13
2
Order By: Relevance
“…2 (b)). We compare our observed trend with previous simulations of short-time diffusivity D ss where a 2 /D ss roughly sets the relaxation time-scale of the system [19,20]. In simulations, D ss decays approximately as D ss ∼ D 0 (1 − bφ) (red line, Fig.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…2 (b)). We compare our observed trend with previous simulations of short-time diffusivity D ss where a 2 /D ss roughly sets the relaxation time-scale of the system [19,20]. In simulations, D ss decays approximately as D ss ∼ D 0 (1 − bφ) (red line, Fig.…”
supporting
confidence: 56%
“…While many previous studies have made analogies between the transport phenomena of colloidal systems and simple liquids [20,24,50,51], we find that the observed Π 2 scaling is actually absent in atomic systems. Specifically, the atomic viscosity (blue curve in Fig.…”
contrasting
confidence: 51%
“…As flow becomes strong, viscosity may continue to decrease if interparticle repulsion is long‐ranged, or may increase if hydrodynamic interactions are strong . Underlying these behaviors are sustained distortions in the microstructural symmetry which can also lead to normal stress differences, osmotic pressure, and flow‐induced diffusion …”
Section: Introductionmentioning
confidence: 99%
“…78 By varying the shear amplitude and frequency separately, large amplitude oscillatory shear is able to disentangle the underlying dynamics that are usually convolved in far-from-equilibrium systems. In contrast to the response in the linear regime, the suspension structure response under large amplitude oscillatory shear demonstrates a nonlinear saturation that arises from shear-induced advection.…”
Section: A Shear Thinning and Thickening Of Colloidal Suspensionsmentioning
confidence: 99%
“…We also showed that in spite of the distinct underlying mechanisms giving rise to the linear and nonlinear responses, all data can be scaled onto a master curve that links small-amplitude oscillatory shear with continuous shear. 78 Finally, we also studied the configurations of particles for large Pe 4000 in the weak shear thickening regime. Reconstructed images show that the suspended particles form a clustered structure.…”
Section: A Shear Thinning and Thickening Of Colloidal Suspensionsmentioning
confidence: 99%